Evaluación de la producción orgánica de brócoli (brassica oleracea var. italica) híbrido legacy, aplicando dos fuentes de microorganismos (azotobacter chroococcum y bacillus subtilis) y tres dosis de abonos orgánicos que activen la solubilidad del fósforo inactivo del suelo en Belisario Quevedo - Cotopaxi - Mena Sigcha, María del Carmen (2014)
This research was conducted in the town Belisario Quevedo at 2750 masl Canton Latacunga in Cotopaxi Province; the overall objective was to evaluate the organic production of broccoli (Brassica oleracea L.) Hybrid Legacy, using two sources of microorganisms ( Azotobacter chroococcum and Bacillus subtilis) and three doses of organic fertilizers. Deductive method was used - experimental variables evaluated were: plant height, diameter and weight of the pellet; the severity and incidence of pests and diseases, the solubility of phosphorus in the soil and yields per hectare obtained in three doses 30, 60 and 90 t / h. , economic analysis was performed to determine the marginal rate of return for each treatment. The experimental design of Randomized Complete Block (RCBD) was applied factorial arrangement of 2 x 3 + 3 with nine treatments and three replications. The best results were obtained : In the plant height 33.08 cm, for the treatment t2....